2019
DOI: 10.3892/mmr.2019.10721
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 silencing aggravates mitochondrial dysfunction in astrocytes under septic conditions

Abstract: Uncoupling protein 2 (UCP2) plays a positive role in sepsis. However, the role of UCP2 in experimental sepsis in astrocytes remains unknown. The present study was designed to determine whether UCP2 has a protective effect in an experimental sepsis model in astrocytes asnd to clarify the mechanisms responsible for its neuroprotective effects after sepsis. An experimental astrocyte model mimicking sepsis-induced brain injury was established using lipopolysaccharide (LPS) and interferon (IFN)-γ. Additionally, UCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…The impact of UCP2 on mitochondrial morphology of the brain tissue after cerebral ischemia and reperfusion has not been reported. Several studies have demonstrated that silencing UCP2 by small interference RNA resulted in more severe mitochondrial swelling, vacuolization and loss of matrix content in cardiomyocytic H9C2 cells and astrocytes compared with control cells challenged with sepsis [47,52,53]. These results support our finding that UCP2 plays an important role in maintaining mitochondrial dynamic and morphological integrity in the brain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The impact of UCP2 on mitochondrial morphology of the brain tissue after cerebral ischemia and reperfusion has not been reported. Several studies have demonstrated that silencing UCP2 by small interference RNA resulted in more severe mitochondrial swelling, vacuolization and loss of matrix content in cardiomyocytic H9C2 cells and astrocytes compared with control cells challenged with sepsis [47,52,53]. These results support our finding that UCP2 plays an important role in maintaining mitochondrial dynamic and morphological integrity in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…The slanting of the mitochondrial dynamics to fission may reduce the mitochondrial network and enhance mitochondrial rupture and induce neuronal cell death after cerebral ischemia [46]. UCP2 silencing has been shown to cause mitochondrial dysfunction in astrocytes under septic conditions [47]. However, it is not known whether UCP2 deletion affects the mitochondrial dynamics in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that more studies are needed to understand what are the differential elements in the response against MPTP intoxication in this species compared to other experimental models. An interesting line to explore could be the neuromelanin, calbindin or UCP2 content of these neurons [ 36 , 37 , 38 , 39 ]. Other emerging questions are the ones related to the catecholaminergic system: are other dopamine-innervated regions altered?…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS induces accumulation of uncoupling protein-2 (UCP2) interferes with ATP synthase and reduces ATP synthesis in renal tubular epithelial cells. The consequent reduction in ATP, autophagy induced apoptosis or necrosis occur followed by the formation of the apoptosome, activation of cytochrome C , caspase activation, and consequently apoptosis ( Duni et al, 2019 ), ( Granata et al, 2015 ), ( Peng et al, 2019 ).…”
Section: Review Findingsmentioning
confidence: 99%